UNIT 11.5 Whole‐Genome Sequencing Analysis Using Next‐Generation Sequencing Data. Issue 12 (2nd May 2016) - Ho, Chi Kent; Cui, Xiaohui; Grubner, Sharon; Larson, Christopher A.; Wei, Ying; Flook, Paul K.
Abstract : Next‐generation sequencing (NGS) technologies have revolutionized the biosciences and become invaluable to the discovery of gene function and its involvement in disease conditions. The fast pace of innovation in NGS technologies has enabled the production of huge volumes of sequence data at progressively lower cost. However, the increasing throughput combined with the growing accessibility of these technologies poses significant challenges for downstream data analysis. Here, we provide an overview of NGS methods and key secondary analysis pipelines with a focus on technology provided by Illumina. As a case study, we highlight potential applications in cancer research. © 2016 by John Wiley & Sons, Inc.